Life-cycle cost-based risk assessment of aging bridge networks. Issue 4 (11th December 2020) - Messore, Matteo Maria; Capacci, Luca; Biondini, Fabio
Abstract: Road infrastructures and bridge networks are becoming increasingly complex systems due to the development of technology in transportation engineering and the continual growth of urban communities. Infrastructure disservice due to seismic events may lead to unacceptable discomfort for commuters. Moreover, network downtime results into economic losses for the affected community, to be quantified in monetary terms by user costs. Seismically vulnerable bridges are also affected by aging and deterioration processes that can reduce the bridge structural performance over time. This paper presents a comprehensive life-cycle cost-based probabilistic framework for seismic risk assessment of spatially distributed aging bridge networks. The seismic risk measure is formulated in terms of annual exceedance rate of a target threshold of user costs. The methodology is applied to a road system in Lombardy region, Italy, reproducing network connectivity and daily travel demands among four major cities and smaller neighbouring municipalities. Despite the area of interest is characterized by low seismicity, the results allow to quantify the impact of aging and deterioration in exacerbating the network seismic risk, highlighting the need for a life-cycle-informed approach to optimal management of infrastructure systems.